Advanced Ceramics and Applications - Gadow, Rainer; Mitic, Vojislav V.; Barbeck, Mike; Barbeck, Mike; Blum, Matthias; Blum, Matthias; Chou, Shang-Shing P.; Chou, Shang-Shing P.; Dimitrijević, Silvana B.; Dimitrijević, Silvana B.; Dimitrijević, Stevan P.; Dimitrijević, Stevan P.; et al. (De Gruyter, 2021)
New ceramic materials are highly appreciated due to their manifold features including mechanical properties, environmental uses, energy applications and many more. This work presents the latest research development and covers a broad range of topics from stabilized zirconia ceramics with enhanced functional properties to ceramic components in medical/biological applications.